Formononetin Activates the Nrf2/ARE Signaling Pathway Via Sirt1 to Improve Diabetic Renal Fibrosis - Zhuang, Kai (Front Pharmacol, 2021)
Oxidative stress is the main factor responsible for the induction of diabetic renal fibrosis. Thus, improving the state of oxidative stress can effectively prevent the further deterioration of diabetic nephropathy (DN). Previous research has shown that formononetin (FMN), a flavonoid with significant antioxidant activity and Sirt1 activation effect, can improve diabetic renal fibrosis. However, the exact mechanisms underlying the effect of FMN on diabetic renal fibrosis have yet to be elucidated. In this study, we carried out in vivo experiments in a db/db (diabetic) mouse model and demonstrated that FMN activated the nuclear factor E2-related factor 2 (Nrf2)/antioxidant response element (ARE) signaling pathway and improved oxidative stress by increasing levels of sirtuin-1 (Sirt1) protein level in renal tissue. We also found that this process reversed the up-regulation of fibronectin (FN) and intercellular adhesion molecule 1 (ICAM-1) and led to an improvement in renal insufficiency. In vitro results further showed that FMN significantly reversed the upregulation of FN and ICAM-1 in glomerular mesangial cells (GMCs) exposed to high glucose. FMN also promoted the expression of Nrf2 and widened its nuclear distribution. Thus, our data indicated that FMN inhibited hyperglycemia-induced superoxide overproduction by activating the Nrf2/ARE signaling pathway. We also found that FMN up-regulated the expression of Sirt1 and that Sirt1 deficiency could block the activation of the Nrf2/ARE signaling pathway in GMCs induced by high glucose. Finally, we found that Sirt1 deficiency could reverse the down-regulation of FN and ICAM-1 induced by FMN. Collectively, our data demonstrated that FMN up-regulated the expression of Sirt1 to activate the Nrf2/ARE signaling pathway, improved oxidative stress in DN to prevent the progression of renal fibrosis. Therefore, FMN probably represents an efficient therapeutic option of patients with DN.